EFEKTIVITAS PENDIDIKAN KARAKTER BERBASIS PANCASILA PADA PELAJAR DAN MAHASISWA - Angelina , Christin; Pandiangan , Inriyani; Simbolon , Lasmaida; Elza Syahri Nst, Nadiyah; Yolanda Br Aritonang , Rumiris; Gabriel Siahaan, Parlaungan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of Pancasila-based character education in shaping the character of students at both the junior high school and university levels. The moral degradation among the younger generation, influenced by globalization and technological advancement, serves as the background for the importance of this study. A qualitative method was employed, with data collection techniques including direct observation, interviews with junior high school students and students of Universitas Negeri Medan, as well as documentation studies from various reputable journals and references. The results indicate that Pancasila-based character education is considerably effective in enhancing students' understanding and application of Pancasila values in academic life, including honesty, discipline, responsibility, cooperation, and mutual respect. However, several obstacles affect the effectiveness of its implementation, including less contextual teaching methods, insufficient supervision from teachers and parents, students' excessive focus on academic grades rather than value application, and low self-awareness in practicing Pancasila values. This study concludes that the success of Pancasila-based character education requires strong synergy between schools, families, and communities, accompanied by innovation in more contextual and student-centered learning strategies.